2019
DOI: 10.1037/cou0000333
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking body image concerns and disordered eating for transgender women: The roles of sexual objectification and minority stress.

Abstract: Transgender women experience gender-based oppression that can take the form of sexual objectification and/or discrimination. These negative experiences may contribute to poorer mental health outcomes (i.e., body dissatisfaction) and physical health outcomes (i.e., disordered eating).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
95
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 80 publications
(166 reference statements)
5
95
1
7
Order By: Relevance
“…In light of research showing that SGMs are at a higher risk for EDs (e.g., Austin et al, , ; Watson et al, ; Williamson, ), Minority Stress Theory (2003) has been applied to demonstrate that experiences of dehumanization and discrimination among SGMs are mediating factors predicting greater disordered eating (Brewster et al, ; Kamody et al, ; Mason & Lewis, ). To advance this research and previous findings about experiences of bullying/abuse among SGMs (e.g., Balsam et al, ; Kann et al, ), we used the minority stress concept to propose increased vulnerability for exposure to abuse and greater ED symptoms in a sample of ED patients receiving treatment in higher levels‐of‐care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In light of research showing that SGMs are at a higher risk for EDs (e.g., Austin et al, , ; Watson et al, ; Williamson, ), Minority Stress Theory (2003) has been applied to demonstrate that experiences of dehumanization and discrimination among SGMs are mediating factors predicting greater disordered eating (Brewster et al, ; Kamody et al, ; Mason & Lewis, ). To advance this research and previous findings about experiences of bullying/abuse among SGMs (e.g., Balsam et al, ; Kann et al, ), we used the minority stress concept to propose increased vulnerability for exposure to abuse and greater ED symptoms in a sample of ED patients receiving treatment in higher levels‐of‐care.…”
Section: Discussionmentioning
confidence: 99%
“…Although this disparity is most consistently found in SGM men (Calzo, Blashill, Brown, & Argenal, ; Diemer, Grant, Munn‐Chernoff, Patterson, & Duncan, ; Morrison, Morrison, & Sager, ), a systematic review of the literature suggested that sexual minority women also tend to have higher rates of ED diagnoses and are at greater risk for engaging in disordered eating behaviors than cisgender heterosexual (CH) women, despite having less body dissatisfaction and drive for thinness (among the two most robust ED risk factors) than CH women and SGM men (Bergeron & Senn, ; Meneguzzo et al, ). Accordingly, researchers have studied several theories, including Minority Stress Theory (Meyer, ) to aid in understanding reasons for these differences (e.g., Brewster, Velez, Breslow, & Geiger, ; Calzo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from living in a cisnormative world, gender‐expansive people are subjected to disproportionate rates of harassment and (sometimes lethal) violence (James et al, ). Transgender women and feminine‐identified gender expansive people can experience transmisogyny from cisgender men—the intersecting axis of sexual objectification, transphobia, and misogyny—and may be particularly at risk if they are transgender women of color (Brewster, Velez, Breslow, & Geiger, ). Furthermore, the lack of institutional or systematic protections for gender expansive people from housing and workplace discrimination fosters a culture wherein unemployment rates are exceedingly high, and in turn, economic insecurity and homelessness is prevalent (James et al, ).…”
Section: Beyond Gatekeeping: Mental Healthcare Providers As Advocatesmentioning
confidence: 99%
“…Due to the unique stressors that they face, nonbinary and genderqueer people may be at even greater risk for poor psychological and physical health outcomes (i.e., anxiety, depression, substance use, suicidality, health risk behaviors, sexual risk behaviors) than transgender people who present with a more binary masculine or feminine appearance (Norcross, Wampold, Budge, & Moradi, ; Clark et al, ; Lefevor, Boyd‐Rogers, Sprague, & Janis, ). Body shame and dissatisfaction, disordered eating, and compulsive exercise are also heightened for gender‐expansive people as they navigate pressure to conform to hegemonic portrayals of masculinity and femininity while also meeting unrealistic standards of attractiveness that all bodies are subject to in US culture (Brewster et al, ; Rankin & Beemyn, ). Psychologists must be aware that body image concerns are commonplace with gender‐expansive populations, yet most literature and resources for such clinical concerns were developed for cisgender women.…”
Section: Beyond Gatekeeping: Mental Healthcare Providers As Advocatesmentioning
confidence: 99%
“…[2][3][4][5] Transgender patients have also reported elevated rates of body dissatisfaction, disordered eating, compensatory behaviors, and self-reported eating disorders compared with the cisgender population. [6][7][8][9][10][11][12][13] unwelcoming physical facilities. 14 As a result, the Internet has become a popular place for the transgender community to seek health-related information.…”
Section: Introductionmentioning
confidence: 99%